Structure and Characterization of 1D Double Chain Copper(II) Complex [Cu(BTZX)2(CH3OH)2]n - Yang, Zhi-Jun; Ni, Tian-Jun; He, Guang-Jie; Huang, Qian-Qian; Yuan, Qiang-Tao; Zheng, Wen-Qi (Asian Journal of Chemistry, 2015)
A novel copper(II) complex [Cu(btzx)2(CH3OH)2]n (1) [btzx = 1,3-bis(tetrazol-1-ylmethyl)benzene] has been synthesized and characterized by elemental analysis, IR and single crystal X-ray diffraction. Results show that in copper(II) complex 1, the Cu(II) atom is eight-coordinated in a elongated octahedron geometry, with four tetrazol N atoms of the ligand and two O atoms of methanol molecules. Ligands in copper(II) complex 1 adopt a trans-conformation acts as a bidentate linker using its two tetrazol groups to coordinate with two Cu atoms extending into an infinite 1D double chain structure. Possible partial p-p stacking interactions involving the tetrazol rings are observed in the crystal structure.